Historia De Vida de la Maestra Josefa María Mendoza Núñez, y Sus Aportes a La Danza Tradicional con en el Grupo de Danza “Las Aguadoras” De San Pelayo – Córdoba (2018)
Knowing the life story of Josefa Mendoza Núñez, from the practice with her "Las Aguadoras", traditional dance group allows me to want to assume a process of inquiry whose main objective is to show the pedagogical methodology used by the teacher, director, founder of the group. Where she has a particular interest in leading artistic creation processes in young people with the goal of preserving and spread the dance traditions of the Carrillo “corregimiento” of San Pelayo (Córdoba). That is why the emphasis is on Porro Palitiao dance, which is important for the culture of this community.